Influencia de la presión de agua y el porcentaje de sólidos en la recuperación de oro mediante concentración gravimétrica centrífuga para un relave tipo óxido procedente de la Provincia de Sánchez Carrión - Santos Ledezma, Elias Francisco (2017)
In this experimental research was studied a rust - type ore from the Province of Sánchez Carrión, whose chemical composition analyzed was 1.35 g / MT Au. These tailings are found to be environmental passives, for which it was proposed to make gravimetric treatment by centrifugal concentration, evaluating the water pressure at 5, 7 and 9 psi, and the percentage of solids at 30, 35 and 40%, then Make the Metallurgical balances to determine the recovery and gold law in the concentrate. From the results obtained it is determined that the solids percentage decreases the recovery and gold law increase, as for the water pressure, the convex curve is generated, obtaining the highest gold recovery of 36.96% with a law of 18, 97 g / MT Gold, at 7 psi water pressure and 30% solids. The lowest recovery was 13.47% gold at 9 psi and 40% solids. The centrifugal gravimetric concentration varying the water pressure and the percentage of solids influence the recovery of gold for a rust-type ore, obtaining a gold law that will allow its commercialization and then make an adequate deposit of said tailings. At 95% significance, the water pressure and the solids percentage significantly influence the gold recovery, but not the interaction, which is not significant, by means of the centrifugal gravimetric concentration.